Yet another acronym - Technology-enhanced Academic Language Support (TALS) - Smith, John (Journal of University Teaching and Learning Practice, 2019)
Since the earliest adoption of educational technologies, teachers and researchers have been exploring its efficacy on language learning and development. The speed with which these technologies are now infiltrating academic student support will continue to increase, and so the need for good guidance in this space will likewise increase. Currently in academic language and learning support, however, the digital space while prevalent and expanding is both poorly defined and the literature widely dispersed. It is argued here that a single term of reference, such as TALS, could provide a centralised meeting point where research and experiences from the field can be more readily and conveniently shared.